Vaccination: the nursing do and the mother and/or caretaker´s knowledge - Vanessa Gomes de Oliveira; Karilena Karla de Amorim Pedrosa; Akemi Iwata Monteiro; Ana Dulce Batista dos Santos (Rev Rene)
It is observed, still nowadays, in the health units’ practice, little knowledge of the mother concerning vaccination and not so much involvement of the nurse in such process. This research aims to identify the nursing actions in the vaccination room and describe the knowledge of mothers or caretakers about childhood vaccination. This type of study is exploratory-descriptive with quantitative approach. The population consisted of 43 mothers and/or caretakers and 10 nurses. It took place in Units of Family Health (USF) in the west area in Natal/RN, in November and December/2008. The majority of the mothers (88.4%) know the importance of vaccination for their children, even though they know which vaccines their children are receiving and for which diseases they are destined. The majority of the professionals give more priority to the techniques than to the educational activity. It is noticed, however, that there are gaps in mothers or caretakers’ knowledge as well as in nursing actions which aim a promotional work in the nursing room.